Construction and validation of clinical scenarios for training informal caregivers of dependent persons - Marcelo da Silva; Patrícia Bossolani Charlo; Aline Zulin; Fernanda Gatez Trevisan dos Santos; André Estevan Jaques; Maria do Carmo Fernandez Lourenço Haddad; Cremilde Aparecida Trindade Radovanovic (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To construct and validate three clinical scenarios for training dependent persons' informal caregivers. Methods: Methodological study, conducted between January and August 2021, in a municipality in the northwest of the state of Paraná. It was developed in two stages: construction of scenarios; and content validation by experts (n = 12). To estimate the degree of agreement between the experts, the content validity index was used, and 80% was considered an acceptable rate of agreement. Results: The simulation scenarios proved appropriate, obtaining an average value of 91.6%. However, some adjustments were made in their organization pertaining clarity in the wording of guidelines, as suggested by the expert validators. Conclusions: The construction and validation of the clinical scenarios proved to be adequate and relevant for use in the training of informal caregivers of dependent persons.